Plant responses and rhizosphere soil characteristics of sea-buckthorn from different sex combinations in an abandoned lead-zinc mine - Gan, Tingjiang; Zeng, Zhenxiong; Pei, Wenhao; Jia, Qi; He, Yunxiao; Chen, Juan (Frontiers in Plant Science, 2025)
BackgroundNowadays, the restoration of abandoned mines has gained more attention due to its significance in vegetation recovery and ecological security Although some studies have indicated the sexual dimorphism of dioecious plants in response to the environmental adaptability, sea-buckthorn (Hippophae rhamnoides L.), a diecious species widely used in afforestation and soil conservation, has not been studied the effects of sexual interactions on degraded ecosystem restoration;MethodsIn situ experiment, the physiological responses and rhizosphere soil changes of sea-buckthorn seedlings from different sex combinations were investigated in an abandoned Lead-Zinc mine;ResultsThe two sexes from intra- and inter-sexual combinations showed differences in chlorophyll content, antioxidant activities, carbohydrates, proline, nutrient elements and zinc content in plants, and total organic carbon, nutrient elements and enzyme activities in rhizosphere soils. The males from the inter-sex combination had stronger antioxidant capacity and more osmoregulatory substances in plants and soil nitrogen contents as well as significantly higher activities of protease and urease with the increases of 139%, and 56%, respectively. In the intra-sex combination, compared with male plants, female plants showed higher contents of total N, Zn, soluble sugar and starch in the roots increased by 30.3%, 75%, 41.5% and 93.7% respectively, as well as higher soil available phosphate and potassium.ConclusionsSexual combinations significantly affected plant responses and soil properties of H. rhamnoides in the abandoned mine, male plants showed better adaptability than female plants in inter-sex combination, while females showed better rhizosphere responses than male plants in same-sex combination, which suggests that sexual interactions of dioecious species should be considered in the restoration of degraded ecosystem.